Framingham cardiovascular risk in patients with obesity and periodontitis - Juliana Rico Pires; Isac Pinheiro dos Santos; Lilian Flosi de Camargo; Elizangela Partata Zuza; Benedicto Egbert Corrêa de Toledo; Sally Cristina Moutinho Monteiro (Wolters Kluwer Medknow Publications, 2014)
Background: Obesity is a chronic inflammatory condition that has been associated to a risk factor for the development of periodontitis and cardiovascular disease; however, the relationship still needs to be clarified. The objective of this study was to evaluate the cardiovascular risk in obese patients with chronic periodontitis. Materials and Methods: A total of 87 obese patients were evaluated for anthropometric data (body mass index [BMI], waist circumference, body fat), systolic blood pressure (SBP) and diastolic blood pressure (DBP), cholesterol, high-density lipoprotein (HDL) and low-density lipoprotein (LDL), triglycerides, glycemia and periodontal parameters (visible plaque index (VPI), gingival bleeding index (GBI), bleeding on probing (BOP), periodontal probing depth (PPD) and clinical attachment level (CAL)). Results: Patients were divided into two groups according to the periodontal characteristics found: Group O-PD: Obese patients with chronic periodontitis (n = 45), 22 men and 23 women; and Group O-sPD: Obese patients without chronic periodontitis (n = 42), 17 men and 25 women. Patients had a BMI mean of 35.2 (±5.1) kg/m 2 . Group O-PD showed a similarity between the genders regarding age, SBP, DBP, cholesterol, HDL, GBI, VPI, PPD ≥4 mm and CAL ≥4 mm. O-PD women showed greater glycemia level and smoking occurrence, but O-PD men presented a 13% - risk over of developing coronary artery disease in 10 years than O-PD women, 9% - risk over than O-sPD men and 15% - risk over than O-sPD women, by the Framingham Score. Conclusions: It was concluded that obesity and periodontal disease are cardiovascular risk factors and that the two associated inflammatory conditions potentially increases the risk for heart diseases.